34.9k views
3 votes
Given g(k) = 2k² - 4, find g(-5).

User Daniel San
by
5.3k points

2 Answers

5 votes

Answer:

g(-5)=46

Explanation:

given that function is,

g(k) = 2k² - 4,

and we find the value of g(-5)

so,

g(-5)=2(5)^2-4

simpley put -5 in place of k

g(-5)=2×25-4

g(-5)=46

User Cynical
by
4.9k points
4 votes

Answer:

g(-5) = 46

Explanation:

Given function:


g(k)=2k^2-4

To find g(-5), substitute k = -5 into the given function:


\begin{aligned}\implies g(-5)&=2(-5)^2-4\\&=2(25)-4\\&=50-4\\&=46\end{aligned}

User Vadiraj Purohit
by
5.5k points